2020
DOI: 10.18295/squmj.2020.20.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Knee Orthosis with Two Degrees of Freedom Joint Design on Gait and Sit-to-Stand Task in Patients with Medial Knee Osteoarthritis

Abstract: Objectives: Knee bracing as a conservative treatment option for patients with medial knee osteoarthritis (KOA) is of great interest to health practitioners and patients alike. Optimal orthotic knee joint structure is essential to achieve biomechanical and clinical effectiveness. Therefore, this study aimed to identify the effects of a knee orthosis with a new two-degrees-of-freedom (DOF) joint design on selected gait parameters and in a sit-to-stand task in patients with mild-to-moderate medial KOA. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Eight studies found that the use of a knee valgus brace significantly improved walking speed, with a maximum increase of 23.53% and a minimum increase of 4.32% [ 26 , 30 32 , 35 , 36 , 38 , 39 ]. However, seven studies reported no significant difference in walking speed when patients wore the brace [ 21 , 27 29 , 33 , 34 , 37 ], and two of those studies even showed negative effects of valgus braces on walking speed [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies found that the use of a knee valgus brace significantly improved walking speed, with a maximum increase of 23.53% and a minimum increase of 4.32% [ 26 , 30 32 , 35 , 36 , 38 , 39 ]. However, seven studies reported no significant difference in walking speed when patients wore the brace [ 21 , 27 29 , 33 , 34 , 37 ], and two of those studies even showed negative effects of valgus braces on walking speed [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The distance in one step is called the step length, and the distance between two consecutive heel contacts of the same foot is called the stride length [ 40 ], as described in Figure 4 . Three studies found that the valgus braces were effective in improving step length and stride length in the arthritic limb, with a maximum increase of 16.90% and a minimum increase of 5.66% [ 26 , 30 , 38 ], as shown in Table 2 , whereas six studies showed that the braces had no significant improvement in step length and stride length [ 27 , 33 , 34 , 39 ] and even had a negative effect on step length due to the restriction of range of motion (ROM) in the sagittal plane [ 21 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations